2019
DOI: 10.18543/tjhe-7(1)-2019pp67-92
|View full text |Cite
|
Sign up to set email alerts
|

Competence-based approach to a module design for the Master Degree Programme in Translation: Challenge of Tuning Russia Tempus Project

Abstract: <p>The article demonstrates the application of the modular competence-based approach for the design of a Master degree programme in translation studies. The case study is based on output materials produced during the lifetime of the Tuning Russia project involving a number of Russian universities, one of which is the Russian State University for the Humanities (RSUH). The module in question – the LSP (language for special purposes) translation module – emphasizes interaction between the related disciplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The literature review has shown that the best solution for students to acquire DC is to integrate them into the formal educational curriculum [1], [2]. This is further supported by [3]- [6] who suggest that education and evaluation of DC should be started from the earliest age of students and promoted throughout the UDC 004:37(497.5) Original Scientific Paper 10.31341/jios.46. 1.11 Open Access curriculum.…”
Section: Introductionmentioning
confidence: 96%
“…The literature review has shown that the best solution for students to acquire DC is to integrate them into the formal educational curriculum [1], [2]. This is further supported by [3]- [6] who suggest that education and evaluation of DC should be started from the earliest age of students and promoted throughout the UDC 004:37(497.5) Original Scientific Paper 10.31341/jios.46. 1.11 Open Access curriculum.…”
Section: Introductionmentioning
confidence: 96%